Influence of primary tumour and patient factors on survival in patients undergoing curative resection and treatment for liver metastases from colorectal cancer. Issue 1 (2nd December 2019) - Scherman, P.; Syk, I.; Holmberg, E.; Naredi, P.; Rizell, M.
Abstract : Background: Resection of the primary tumour is a prerequisite for cure in patients with colorectal cancer, but hepatic metastasectomy has been used increasingly with curative intent. This national registry study examined prognostic factors for radically treated primary tumours, including the subgroup of patients undergoing liver metastasectomy. Methods: Patients who had radical resection of primary colorectal cancer in 2009–2013 were identified in a population‐based Swedish colorectal registry and cross‐checked in a registry of liver tumours. Data on primary tumour and patient characteristics were extracted and prognostic impact was analysed. Results: Radical resection was registered in 20 853 patients; in 38·7 per cent of those registered with liver metastases, surgery or ablation was performed. The age‐standardized relative 5‐year survival rate after radical resection of colorectal cancer was 80·9 (95 per cent c.i. 80·2 to 81·6) per cent, and the rate after surgery for colorectal liver metastases was 49·6 (46·0 to 53·2) per cent. Multivariable analysis identified lymph node status, multiple sites of metastasis, high ASA grade and postoperative complications after resection of the primary tumour as strong risk factors after primary resection and following subsequent liver resection or ablation. Age, sex and primary tumour location had no prognostic impact on mortality after liver resection. Conclusion: Lymph node status and complications have a negative impact on outcome after both primary resection and liver surgery. Older age and female sex were underrepresented in the liver surgical cohort, but these factors did not influence prognosis significantly. Abstract : Prognostic factors for the primary colorectal tumour also affect the outcome after surgery for liver metastases. Although performance status and complications after primary resection also influence outcome after liver resection, other factors such as older age and female sex do not, but these patients are still underrepresented in the liver surgical cohort. Awareness of the prognostic impact in both cohorts will improve decision‐making. Information from primary surgery influences liver resection outcomes. Abstract : Antecedentes: Para curar el cáncer colorrectal es necesaria la resección del tumor primario, pero cada día es más frecuente la realización de una metastasectomía hepática con intención curativa. Este estudio basado en un registro nacional analizó los factores pronósticos para los tumores primarios tratados con intención curativa, incluido un subgrupo de pacientes a los que se realizó una metastasectomía hepática. Métodos: En el registro poblacional sueco de cáncer colorrectal se identificaron los pacientes a los que se realizó una resección primaria radical entre 2009‐2013 y se cotejaron con un registro de tumores hepáticos. Se obtuvieron los datos sobre el tumor primario y las características del paciente, y se analizó su influencia en el pronóstico. Resultados: Se identificaron 20.853 pacientes con resección radical, de los que en un 38, 9% se realizó la resección o ablación de metástasis hepáticas. La supervivencia relativa a 5 años, estandarizada por edad, después de la resección radical del cáncer colorrectal y después de la cirugía de las metástasis hepáticas colorrectales fue del 80, 6% (i.c. del 95% 79, 8‐81, 3) y del 49, 6% (i.c. del 95%: 46, 0‐53, 2), respectivamente. El análisis multivariable identificó la invasión ganglionar, las metástasis en varias localizaciones, una puntuación ASA alta y las complicaciones postoperatorias después de la resección del tumor primario como factores de riesgo tanto de la resección primaria como de la resección o ablación hepática. No tuvieron influencia sobre la mortalidad tras de la resección hepática ni la edad, el sexo o la ubicación del tumor primario. Conclusión: El grado de invasión linfática y las complicaciones después de la resección primaria tuvieron un impacto negativo en los resultados tanto de la cirugía primaria, como de la cirugía hepática. Si bien la edad avanzada y el sexo femenino estaban infrarrepresentados en la cohorte de cirugía hepática, estos factores no influyeron significativamente en el pronóstico.